2019
DOI: 10.2139/ssrn.3497399
|View full text |Cite
|
Sign up to set email alerts
|

Wealth Inequality in Central and Eastern Europe: Evidence From Joined Household Survey and Rich Lists’ Data

Abstract: ic ch ha al l B Br rz ze ez zi in ns sk ki i a a * *, , K Ka at ta ar rz zy yn na a S Sa ał ła ac ch h a a , , M Ma ar rc ci in n W Wr ro oń ńs sk ki i b b

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…The major limitation of their study, however, was the use of the Survey of Health, Ageing and Retirement in Europe (SHARE) data, which covers only the population aged 50 and above. Skopek et al's (2014) results are in line with those of Brzeziński et al (2020), who use the HFCS data for 2013/2014 and analyse entire populations of the selected CEE countries.…”
Section: Wealth Inequality In Post-socialist Transition Countriessupporting
confidence: 80%
See 4 more Smart Citations
“…The major limitation of their study, however, was the use of the Survey of Health, Ageing and Retirement in Europe (SHARE) data, which covers only the population aged 50 and above. Skopek et al's (2014) results are in line with those of Brzeziński et al (2020), who use the HFCS data for 2013/2014 and analyse entire populations of the selected CEE countries.…”
Section: Wealth Inequality In Post-socialist Transition Countriessupporting
confidence: 80%
“…Empirical studies have shown that due to this 'missing rich' phenomenon the top 1% wealth share in such countries as Austria or Germany is underestimated by as much as 8-10 percentage points (Bach et al 2019;Vermeulen 2018). In our companion paper, we show that the size of analogous corrections for most of the CEE countries range from 7 to 15 percentage points in case of top 1% share, and from 4 to 11 percentage points in the case of Gini index (Brzeziński et al 2020).…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations